Coping strategies of mothers with preterm babies admitted in a public hospital in Cape Town - Delphine A. Sih; Million Bimerew; Regis R.M. Modeste (AOSIS, 2019)
Background: Most pregnancies run a normal course, ending in a healthy mother-infant relationship, but sometimes, it can also be a life-threatening and stressful condition. The stress levels of mothers are more aggravated when they deliver preterm babies. Objectives: To explore the coping strategies of mothers of preterm babies with the stress of preterm delivery and subsequent admission of the preterm neonate to a neonatal care unit. Method: A qualitative research approach applying an exploratory and descriptive design was applied to explore the coping strategies of mothers with preterm babies admitted in a neonatal care unit. The study applied a purposive sampling technique to select mothers with preterm babies. The population for this study included women who delivered preterm babies and whose babies were admitted in the neonatal care unit at a public hospital in Cape Town. Semi-structured interviews were conducted until data saturation was reached, and 11 mothers with preterm babies in the selected public hospital participated in the study. Data were analysed manually using thematic content analysis with an inductive approach. Results: Results were deductively interpreted and supported by the Brief COPE model. The main themes that emerged from data analysis included praying, attachment with baby and acceptance of the situation. Under praying the following subthemes emerged, namely praying for God's strength, God's grace, babies' survival and thanksgiving to God for babies' health and preferred gender. The theme of attachment with the baby emerged with the following subthemes: bonding with the baby and seeing the baby. The last theme that was acceptance of the situation emerged with the following subtheme: perseverance in the situation and mother's awareness of her responsibility. Conclusion: Even though the mothers of preterm babies cope differently after delivery, their coping abilities, which included praying, attachment to baby and acceptance of the situation, were greatly determined by the condition of their babies as well as the support they receive from significant others.